2018
DOI: 10.1007/s10067-018-4274-0
|View full text |Cite
|
Sign up to set email alerts
|

A Chinese case series of Yao syndrome and literature review

Abstract: Yao syndrome (YAOS), formerly named NOD2-associated autoinflammatory disease, is a periodic disease characterized by fever, dermatitis, polyarthritis, distal extremity swelling, and gastrointestinal and sicca-like symptoms associated with specific NOD2 sequence variants. All patients in the literature were Caucasians. Herein, we report the first case series of YAOS in China to further expand the clinical and genetic characteristics of this disorder. A retrospective review of patients who were diagnosed with YA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Also, the cells of the patients had high basal IL-6 levels which were increased by muramyl dipeptide stimulation, indicating that NOD2 expression and pathway activation are aberrant in YAOS. 242 In a case series, 241 genetic testing in three YAOs patients detected presence of the following heterozygous NOD2 variants:…”
Section: Yao Syndromementioning
confidence: 99%
See 2 more Smart Citations
“…Also, the cells of the patients had high basal IL-6 levels which were increased by muramyl dipeptide stimulation, indicating that NOD2 expression and pathway activation are aberrant in YAOS. 242 In a case series, 241 genetic testing in three YAOs patients detected presence of the following heterozygous NOD2 variants:…”
Section: Yao Syndromementioning
confidence: 99%
“…The molecular mechanisms and underlying pathogenesis of YAOS are unclear, but there is a genetic association with certain NOD2 variants. 239 , 241 A study that examined NOD2 expression and activation of signaling pathway reported that NOD2 transcript level and basal p38 mitogen-activated protein kinase activity was elevated in peripheral blood mononuclear cells from IVS8 + 158 YAOS patients. Also, the cells of the patients had high basal IL-6 levels which were increased by muramyl dipeptide stimulation, indicating that NOD2 expression and pathway activation are aberrant in YAOS.…”
Section: Yao Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…YAOS, formerly termed NOD2 -associated autoinflammatory disease (NAID), is a polygenic AID characterized by recurrent fever, dermatitis, arthritis, swelling of the distal extremities, gastrointestinal and sicca-like symptoms with eyelid swelling. [ 44 ] The disorder has a genetic association with certain NOD2 variants. [ 45 ] Intermittent dermatitis develops in 90% of YAOS patients, which often manifested as erythematous patches, flushing, and plaques ( Figure 1I ).…”
Section: Autoinflammatory Urticarial Dermatosismentioning
confidence: 99%
“…14 The disease is reported in North America, 15 Europe, 16,17 and Asia. 18 With the disease being increasingly recognized among the medical community, we have gained first-hand experience and advanced knowledge on the disease. Herein, we report new clinical and molecular data to expand the spectrum of YAOS.…”
mentioning
confidence: 99%